Impact-resistance of bio-inspired functionalized polyether-ether-ketone implant for cranioplasty - Coyle, Dylan; Zumbo, Bianca; Moritz, Niko; Frantzén, Janek; Aitasalo, Kalle; Turco, Gianluca; Kulkova, Julia (Elsevier BV, 2026)
This study introduces Amanita, a pioneering bionic design for a fully 3D-printed cranial implant made of polyether-ether-ketone (PEEK) functionalized with bioactive glass granules. The mechanical integrity of cranial implants is crucial for effective brain protection. The primary aim was to evaluate the mechanical resistance of this innovative implant to validate its functionality for cranial protection. We employed a standardized biomechanical testing protocol to assess the mechanical properties of the Amanita implants. The implants were subjected to impact forces that simulated real-life blunt trauma scenarios to test their performance under stress. The Amanita implants exhibited significant resilience under compressive forces, withstanding over 100 N at a 2 mm deflection and effectively absorbing more than 1000 mJ at a 6 mm deflection. Furthermore, these implants maintained structural integrity without catastrophic failure at deflections up to 10 mm. The findings validate the design and manufacturing approach of the Amanita implants, demonstrating their potential for clinical use in cranioplasty. The implants showed adequate impact resistance, potentially lowering the risk of injury from falling objects or blunt trauma. Additionally, the adoption of additive manufacturing techniques enables the production of these implants on-site at hospitals, promoting socially and environmentally sustainable healthcare solutions.